Intercultural Sensitivity Among Undergraduate Students in Universitas Jambi - Melati , Melati; Fuad Sabri, Munif; Armiwati, Armiwati (International Journal of Language Teaching and Education, 2023)
The concerns about globalization are undoubtedly in this era. Every individual has experienced globalization and cultural diversity. Along with that, every individual must be able to adapt to those of different cultures, backgrounds, and behaviors. Furthermore, being able to comprehend other cultures is crucial where various new cultures have been introduced through globalization which requires us to adjust our behavior towards these cultures. In line with this issue, in this research, the researcher focused on analyzing the intercultural sensitivity level of FKIP students in Universitas Jambi. In this study, the researcher used a quantitative approach, and in the research design, the researcher applied the survey method with descriptive statistic analysis. The research participants were selected using purposive sampling. The data were gathered via a questionnaire. The result of this study showed that the student's level of intercultural sensitivity is moderate. This result also demonstrates that students have acquired a degree of intercultural sensitivity that is quite satisfactory.